Research of the Torsion Stiffness of Involute Gear Transmission - Zhou Xin; Deng Kangyao; Tian Zhongxu; Hu Lifeng (Jixie chuandong)
The gear stiffness calculation has important significance for the study of noise and vibration of power transmission system. Based on the finite element calculation of the software Abaqus,the torsional mesh stiffness of spur gear with involute profile is studied. In the study,the relationship between teeth is processed by using the contact model,the meshing torsional stiffness result of single tooth model under multiple states in the entire engagement cycle is obtained. The Ishikawa formula for gear stiffness calculation is analyzed and the calculation result is compared with the gear stiffness calculated by the finite element method,and the accuracy and error sources are analyzed. The meshing stiffness of the full gear model is calculated by using the finite element contact model,the variation of spur gears meshing stiffness is obtained. Based on the FEM results of the spur gear,a fast calculation method for meshing torsional stiffness of helical gear is given.